The Influence of the Local and General Environment on the Use and Distribution of Drugs by Adolescents in Belgrade - Radovanović, Ivana D.; Spasić, Danijela; Maljković, Marija (NBP. Nauka, bezbednosti, policija, 2023)
The aim of the work was to determine if there are significant differences in the variables of the local and general environment between adolescents who have not had any contact with drugs and those who use and distribute drugs. The examination of these differences was carried out on a two-stage random sample of secondary school students in Belgrade, 1286 students between the ages of 15 and 19. All data were collected by a specially constructed questionnaire in a completely anonymous situation. The analysis of the obtained data on the differences between adolescents without contact with drugs and those who use and distribute drugs was done by canonical discriminant analysis, separatelly for boys and for girls. In the analysis of differences, one significant discriminative function was obtained for boys, whose canonical correlation was of the order of .616. That function is defined by the ease of drug availability in the local environment (.863 and .874), but some other variables of the local and general environment also played a significant role in the structure of that function. In girls, one discriminative function was also isolated, the correlation of which is lower than in boys (.540). That function is also defined by the ease of availability of drugs (.719 and .737), but also by some other variables, whereby differences can be observed in relation to the structure of this function in boys. Research data undoubtedly show that when choosing preventive interventions related to drug abuse, special attention must be paid to the form of abuse that manifests itself as the simultaneous use and distribution of drugs, and to the factors from these two environments that influence that behavior, as well as to differences in risk and protective factors depending on gender.